Analisa transient structural disc-brake dengan material yang berbeda menggunakan software finite element - Abbari, Arif Dzaky; Gusniar, Iwan Nugraha; Setiawan, Reza (Patria Artha Technological Journal, 2021)
One of the causes of traffic accidents is the vehicle factor caused by the brake system that is not functioning properly. Brakes are a very important component in a vehicle, its function is to reduce the kinetic energy of the vehicle where the safety of the driver is very dependent on this component. Materials are very important role in the design of disc brakes, the main factor in the braking process is friction, and each material has its own friction coefficient. In the automotive industry there are many types of disc brake materials, so it is necessary to conduct a more indepth study on the effect of the disc brake material to determine the deformation, stress and strain that happen during the braking process. The method we used is to design a disc brake on solidworks and simulate it in ansys 19.2 software to find the structural transient values of gray cast iron, aluminum alloy, stainless steel, and titanium alloy materials. The result of this research is a data on the transient structural disc brake of the Vario 125 CBS motorcycle with the highest maximum total deformation happens in the gray cast iron material of 8.4965 mm. For the maximum value of equivalent elastic strain, the highest happens in aluminum alloy material at 0.012275 mm/mm. For the highest maximum equivalent stress value happens in stainless steel material at 1494.3 Mpa.